KAJIAN TENTANG MANUSIA - Arifan Ananda; Wedra Aprison (ADISAM PUBLISHER, 2023)
This article delves into the fundamental components of educational scholarship, focusing on the concept of human nature within the realm of Islamic thought. Recognizing five key elements in educational studies—namely, the concept of humanity, educational goals, learners, educators, and the learning process—the article places particular emphasis on the concept of humanity. Human beings, considered unique and enigmatic creatures, possess the dual capacity to be educated (as learners) and to educate (as educators), making them central to the aims and processes of education. The article draws from various perspectives, including philosophical and Quranic viewpoints, to elucidate the profound nature of humanity. From a philosophical standpoint, ancient Greek philosophers such as Plato and Aristotle are invoked to explore the complexities of the human body and soul. Islamic philosophers like Ibn 'Arabi and Al-Farabi are also referenced to highlight the significance of human intellect and spirituality. In the context of Islam, the quest for self-discovery through intellectual capabilities becomes imperative. The Quranic perspective underscores the importance of contemplating one's essence and encourages seeking truth through reference to the Quran as the foundational framework for Islamic thought. Methodologically, this article adopts a literature review approach, specifically a critical descriptive analysis. Drawing from a range of educational experts' articles and journals, the research aims to unravel the Quranic perspective on the essence of humanity. The results and discussions section explores the linguistic and terminological origins of the term